Empathy and the Aesthetic Mind : Perspectives on Fiction and Beyond - Kyprianidou, Efi; Bantinaki, Katerina; Vassiliou, Fotini (My University, 2025)
Few ideas have been so widely accepted as the idea that art transports us to other places and times and oﬀers new perspectives as we ﬂoat between real and ﬁctional worlds. In reading Pride and Prejudice, we feel absorbed in life in nineteenth-century Regency England; in seeing Gericault’s Raﬅ of the Medusa, we immerse ourselves in the horrors of the shipwreck that shook France’s political and social life by 1816. Sometimes, this deep and vivid immersion in an artwork aﬀords, in the words of Rae Langton (2019: 78), a ‘shiﬅ in self-location’, a sense of ﬁrst-personal presence in alien experiences: we not only see the world through an other’s lenses, but we aﬀectively and/or cognitively relate to experiences that primarily belong to someone else. is remarkable phenomenon is invariably called empathy, whether manifested in everyday experience or the experience of art. e aim of this volume is to probe the character and role of empathy in our engagement with diﬀerent forms of art, but also its signiﬁcance beyond the artistic encounter: its value for cognition, our emotive life and our moral stance.